A Discourse of Drupadi Character in Javanese Puppetry in “Feminism Perspective” - Dwi Purbo Cahyono Nuswantoro; Titis Srimuda Pitana; Susanto Susanto (Universitas Sebelas Maret, 2022)
Javanese puppetry story is still dominated by masculine perspective, in which men have higher degree than women. It creates a social construction that the position of women is under that of men and women has not control over their body. From this representation of ideology, women’s feminism spirit grows to get equality and control or power over themselves. Drupadi character symbolizes a Javanese woman subjected to the man’s power. It contains internal interpretation on a strongly constructed awareness that the position of women is under that of men. The discourse was constructed through the life journey of Drupadi character who was always subjected to her husband’s command. Drupadi tried to do all of his husband’s command and decision toughly and indirectly Drupadi no longer has control over her body. The research method used was qualitative research and data analysis technique used was descriptive one with hermeneutic approach. This research will operate the conception and its relation to the text interpretation. Using this research analysis method, discourse and feminism theories will be used to study the character of Drupadi in Javanese puppetry. Meanwhile, data validation was carried out using triangular data through: firstly comparing the data of observation and data of interview; secondly, comparing information coming from one source with that coming from another; and thirdly, comparing interview with relevant document.